Repositioning of Difluorinated Propanediones as Inhibitors of Histone Methyltransferases and their Biological Evaluation in Human Leukemic Cell Lines - Pal, Tanushree; Sharda, Asmita; Khade, Bharat; Ramaa, C. S.; Gupta, Sanjay (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: At present, ‘pharmaco-epigenomics’ constitutes the hope in cancer treatment owing to epigenetic deregulation- a reversible process and playing a role in malignancy. Objective: Chemotherapy has many limitations like host-tissue toxicity, drug resistance. Hence, it is imperative to unearth targets to better treat cancer. Here, we intend to repurpose a set of our previously synthesized difluorinated Propanediones (PR) as Histone lysine Methyltransferase inhibitors (HMTi). Methods: The cell lines of leukemic origin viz. histiocytic lymphoma (U937) and acute T-cell leukemia (JURKAT) were treated with PR-1 to 7 after docking studies with active pocket of HMT. The cell cycle analysis, in vitro methylation and cell proliferation assays were carried out to delineate their physiological role. Results: A small molecule PR-4, at 1 and 10μM, has shown to alter the methylation of histone H3 and H4 in both cell lines. Also, treatment shows an increase in G2/M population and a subsequent decrease in the G0/G1 population in U937. In JURKAT, an increase in both G2/M and S phase population was observed. The sub-G1 population showed a steady rise with increase in dose and prolonged time intervals in U937 and JURKAT cell lines. In SRB assay, the PR showed a cell growth of 42.6 and 53.4% comparable to adriamycin; 44.5 and 53.2% in U937 and JURKAT, respectively. The study suggests that PR-4 could emerge as a potential HMT inhibitor. Conclusion: The molecule PR-4 could be a lead in developing more histone lysine methyltransferases inhibitors with potential to be pro-apoptotic agents.
Keywords: anti-cancer